Adaptação e validação da escala de motivação à prática de atividades físicas - Gonçalves, Marina Pereira (2008)
The study of the motivation to practice physical activities is relevant once through this it is possible to develop intervention strategies for sedentary population. In this way, the present dissertation aimed to adapt and validate for the Brazilian context the Motives for Physical Activity Measure Revised (MPAM-R). It was investigated yet the relation of some socio-demographic variables (age, gender, Body Mass Index - BMI, types of physical activity; way to practice and time of practice) and the participants means in the motives studied. The physical activity (PA) is defined as any bodily movement produced by skeletal muscles resulting in energy expenditure above the basal level. However, in the present study it was considered motivation for two types of PA: the physical exercises and sports. The Self-Determination Theory (SDT) underlay this research, once it has been used in the sportive context, beyond the facto of it was used as theoretical base to the development of MPAM-R. To attain the proposed goals, it was accomplished translations to Portuguese of the original English scale. Next, was carried out the semantic analysis and the judge analysis. For the empirical analysis of items, participated 309 practitioner of PA, classified in physical exercises practitioners and sports practitioners, with ages between 16 and 74 years, distributed equally by sex. They answered the final version in Portuguese of the MPAM-R and socio-demographic questions. The data was collected in Natal/RN, where the researcher approached people in some places where the PA is practiced, following she communicated that their involvement will be spontaneous and their responses will be confidential. The obtained results pointed the confirmation of the existence of five factors in the final version of the instrument, that was composed by 26 items that presented the following statistics indexes: x² (289) = 757.75, p < 0.000, x²/DF = 2.62, with GFI of 0.83, AGFI of 0.80 and RMSEA of 0.07. The reliability (Cronbach Alpha) of the complete instrument was 0.90, and the indexes of each factor were considered satisfactory too: Enjoyment (α = 0.88), Health (α = 0.84), Appearance (α = 0.79), Competence (α = 0.85) and Social (α = 0.75). It was observed that, in general, the main motive presented by the participants to practice PA was Health. It was verified yet, that women and aged had a higher mean in the Health factor; among the exercise practitioners was found a higher mean in the Appearance factor; and a higher mean in the Social factor was found among those that practice PA with accompaniment. It was concluded that the MPAM-R presented satisfactory psychometric parameters, became it useful in futures researches. Moreover, proposed the accomplishment of new studies that considered others variables to the intent of the better understanding of motivation to practice physical activity